Bioactive nutraceuticals and dietary supplements in neurological and brain disease : prevention and therapy - Watson, Ronald R. (Ronald Ross); Preedy, Victor R. (Academic Press, 2015)
Nutritional supplement research concerning brain health and neurological disease is becoming an important focus. While nutritional supplements are very popular for general health and well being, the effectiveness of common supplements and their impact on general brain health and for the treatment or prevention of neurological disease is not clearly understood. This comprehensive introduction to bioactive nutraceuticals for brain and neurological provides a foundation review for research neuroscientists, clinical neurologists, pharmacology researchers and nutrition scientists on what we know n.